Multiple Low Doses of Intravenous Corticosteroids to Improve Early Rehabilitation in Total Knee Arthroplasty: A Randomized Clinical Trial - Li, Donghai; Zhao, Jinhai; Yang, Zhouyuan; Kang, Pengde; Shen, Bin; Pei, Fuxing (The Journal of Knee Surgery, 2019)
Low doses of corticosteroids have been proved to be effective in decreasing the inflammatory cytokines and relieving the pain. However, the optimal dosage of corticosteroids in total knee arthroplasty (TKA) is undetermined. A total of 103 patients were randomly divided into three groups. Group A containing 32 patients received normal saline. Group B including 36 patients used two doses of 100 mg hydrocortisone, given 2 hours before and 8 hours after surgery. Group C involving 35 patients received four doses of 100 mg hydrocortisone, 8 hours apart.The level of interleukin 6 (IL-6) and C-reactive protein (CRP) were lower in group C than those in group A when detected at 12, 24, and 48 hours after operation and even lower than that in group B at 24 and 48 hours (p < 0.05, all). The visual analog scale (VAS) pain scores were significantly reduced by using two doses of hydrocortisone at the first 12 hours compared with group A (p > 0.05), but it did not show statistic difference 24 hours later (p > 0.05). For comparison, patients with multiple doses achieved continuously better outcomes on pain management than the blank control group within postoperative 36 hours at rest and at 24 hours with activity. In addition, patients using multiple doses of hydrocortisone achieved fewer occurrences of nausea and vomiting, fever, and sleeplessness, better knee function recovery, better patient satisfaction, and shorter length of hospital stays (p < 0.05, all).Multiple dose of hydrocortisone was benefit to the pain management and early rehabilitation in TKA and may be recommended to the clinical practice.
Keywords: total knee arthroplasty; pain; hydrocortisone; rehabilitation